Clinical, Biochemical, and Molecular Characteristics of Filipino Patients with Tyrosinemia Type 1 - Barbra Charina V. Cavan; Leniza G. de Castro-Hamoy; Conchita G. Abarquez; Ebner Bon G. Maceda; Maria Melanie Liberty B. Alcausin (MDPI AG, 2024)
Hereditary tyrosinemia type I (HT1), or hepatorenal tyrosinemia, is an amino acid disorder which may cause hepatic failure as well as renal and neurologic comorbidities. Early detection of this disorder is possible with newborn screening (NBS). The objective of this study is to describe the clinical, biochemical, and molecular characteristics of Filipino patients diagnosed with HT1 through the expansion of the Philippine NBS program in 2014. There were a total of 16 patients with confirmed HT1 from then until September 2022. Clinical and biochemical data during confirmation and initial evaluation, as well as molecular data, were obtained from the patients' medical records. The cohort included children between the ages of 18 and 54 months at the time of data collection. The mean age at treatment initiation was 26.8 days. The mean succinylacetone level from dried blood spot sampling using tandem mass spectrometry (MS) was 11.1 µmol/L. Biochemical confirmatory tests via plasma amino acid analysis showed mean levels of tyrosine, phenylalanine, and methionine of 506.1 µmol/L, 111.5 µmol/L, and 125.4 µmol/L, respectively. Upon urine organic acid (UOA) analysis, succinylacetone was detected in all except for one patient, who was managed prior to UOA analysis. The most common clinical characteristics were abnormal clotting times (62.5%), elevated alpha fetoprotein (37.5%), anemia (31.3%), and metabolic acidosis (31.3%). The most common genotype was homozygous c.122T>C p.Leu41Pro in 64.3% of patients. The allelic frequency of this pathogenic variant is 71.4%. The inclusion of HT1 in the Philippine NBS program allowed early diagnosis and management of HT1 patients.